Pengaruh Program Keselamatan dan Kesehatan Kerja Terhadap Kepuasan Karyawan pada PT PLN (Persero) Unit Pelaksana Pelayanan Pelanggan Makassar Utara di Makassar - Arryad Firdauzi Ramly; Amiruddin Tawe; Zainal Ruma; Romansyah Sahabuddin; Uhud Darmawan Natsir (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the effect of occupational safety and health program on employee satisfaction at PT PLN (Persero) North Makassar customer service implementation unit in Makassar. This research is a quantitative study with a descriptive approach and is a population study. The sample in this study were employees at the office of PT PLN (Persero) North Makassar customer service implementation unit in Makassar as many as 35 people. Hypothesis testing in this study using multiple linear regression tests and get results, namely: Based on the results of hypothesis testing using multiple linear regression analysis tests, it shows that work safety and occupational health variables simultaneously affect employee satisfaction at PT PLN (Persero) North Makassar customer service implementing unit in Makassar. The results of hypothesis testing also show that work safety partially affects employee satisfaction at PT PLN (Persero) North Makassar customer service implementing unit in Makassar and occupational health partially affects employee satisfaction at PT PLN (Persero) North Makassar customer service implementing unit in Makassar.